Caffeine-Mediated Combustion Synthesis of Nanocrystalline ZnO and NiO for Degradation of Efficient Methyl Orange - Kamalaveni, K.; Ilamparithi, A. (Asian Journal of Chemistry, 2026)
Caffeine-mediated ZnO and NiO nanoparticles were prepared through an eco-friendly solution combustion route. The synthesis yielded porous, nanocrystalline powders with high chemical purity and appreciable photocatalytic performance. X-ray diffraction patterns assigned the ZnO phase to the hexagonal wurtzite structure and the NiO phase to the cubic bunsenite structure. The crystallite dimensions estimated from the Scherrer equation were 31.2 ± 2.8 nm for ZnO and 22.9 ± 1.9 nm for NiO. FT-IR spectra contained the characteristic metal–oxygen vibrational bands corresponding to Zn–O and Ni–O bonds, confirming the formation of the oxide phases. Scanning electron microscopy (SEM) revealed irregular, porous particles with a tendency toward agglomeration at the nanoscale. Energy-dispersive X-ray spectroscopy detected the expected elemental constituents and confirmed the high purity of the synthesized materials. The optical band-gap energies calculated from UV-DRS absorption data were 2.98 eV for ZnO and 3.10 eV for NiO. Photoluminescence measurements revealed blue emission features associated with oxygen vacancy related defects and other localized electronic states. ZnO exhibited comparatively weaker emission intensity, which is consistent with a lower extent of photogenerated electron-hole recombination. The photocatalytic properties were assessed through the degradation of methyl orange under UV irradiation. ZnO attained 83.2% dye degradation within 120 min, while NiO achieved 77.56% degradation after 150 min.